Implementasi Media Berbasis Teknologi dalam Pembelajaran PPKn untuk Meningkatkan Motivasi Belajar Siswa di SMP Negeri 1 Gorontalo - Muhamad Surya Pratama Ahmad; Zulaecha Ngiu; Yuli Adhani (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2026)
The aim of this research is the low learning motivation of students in Pancasila and Citizenship Education courses due to teaching methods that are still traditional and less participatory. This research aims to increase student learning motivation by utilizing technology-based learning tools such as Curipod and Quizizz. The two Classroom Action Research (PTK) design cycles used in this research are the planning, action implementation, observation and reflection stages. Class IX.6 students of SMP Negeri 1 Gorontalo City were used as research subjects. Data collection techniques include observation, surveys and recording. Based on the research results, students' learning motivation increased significantly from 64.04% in the pre-cycle to 82.22% in the first cycle and 82.57% in the second cycle. These findings indicate that the use of interactive digital learning materials can increase students' levels of activity, excitement, and engagement. The results of this research show that, despite continuing to emphasize technology readiness and efficient learning management, incorporating technology into the classroom can increase student interest and learning outcomes.